The incidence of pokkah boeng in indigenous and exotic sugarcane (Saccharum officinarum) clones - KARUPPAIYAN, R; RAM, BAKSHI; RAMDIYA, S; ALI, MASAWWAR; MEENA, M R (The Indian Journal of Agricultural Sciences, 2015)
Pokkah boeng (Fusarium moniliforme J L Sheldon) is a minor fungal disease in sugarcane (Saccharum officinarum L.), characterized by malformed leaves. The disease incidence was surveyed at two locations in Haryana (Karnal and Kaithal) from 2010 to 2013. Chlorotic phase infection was prevalent in the study area. The percent disease incidence ranged from 6.90 to 25.30%, the highest incidence was recorded during 2013. A total of 138 subtropical sugarcane varieties, 40 pre-release clones and 182 exotic clones were screened against the disease under natural epiphytotic condition at Karnal. Most of the clones (80.83%) were resistant (120 clones out of 360) or moderately resistant (171 clones out of 360) to pokkah boeng. Subtropical varieties such as BO 137, Co 0238, CoH 110, CoJ 83, CoJ 85, CoS 8432, CoS 8436, CoS 88230, CoS 03251, CoS 03252, CoSe 95436, CoSe 01434 and UP 0097 were moderately susceptible hence strong seed health programme is suggested to contain the disease. Fourteen clones, viz. Co 425, Co 12027, Co 10036, Co 0331, M 165/38, H 45-2120, B 46-199, Q 64, PR 1058, CP 81-1384, F 65-554, POJ 6688, EPC 37-069 and H 44-3098 were susceptible to pokkah boeng hence this information may be taken into account while deciding the merit of the clones for hybridization. Autumn planted canes manifested less disease incidence than spring planted canes. Canes around field border and broad leaved clones showed higher disease incidence. However, the incidence did not vary between plant crop and ratoon crops. There were no association between pokkah boeng incidence and top borer attack but their combined damage would be detrimental to the crop. About 92.67% of pokkah boeng infected plants recovered growth, without fungicide spray, as the age of the crop advances and with change in weather.